Aging impairs ischemia-induced neovascularization by attenuating the mobilization of bone marrow-derived angiogenic cells. (September 2016) - Lam, Yuen Ting; Lecce, Laura; Clayton, Zoe; Simpson, Philippa J.L.; Karas, Richard H.; Ng, Martin K.C.
Abstract: Background: Aging is associated with impaired ischemia-induced neovascularization. However, the effects of aging on bone marrow-derived angiogenic cell (BMDAC)-mediated vasculogenesis and on angiogenesis at the ischemic sites remain incompletely understood. Methods and results: Two- and 24-month old male C57Bl/6J mice were subjected to hindlimb ischemia. The levels of Sca1 +/CXCR4 + BMDACs were determined post-ischemia by flow cytometry. In young mice, ischemia increased Sca1 +/CXCR4 + BMDAC levels in the bone marrow and spleen at day 3 (p < 0.001) and in the circulating blood at day 7 (p < 0.01) post-ischemia. However, ischemia-induced elevation of progenitor cells was attenuated in the bone marrow, spleen and blood of old mice despite a preserved HIF-1α-mediated angiogenic response in the ischemic tissues. Irradiated young recipient mice engrafted with old bone marrow displayed reduced levels of Sca1 +/CXCR4 + BMDACs in the bone marrow and circulating blood post-ischemia compared to recipients with young bone marrow. Ex vivo cultured BMDACs from old mice exhibited reduced SDF-1-stimulated migration (p < 0.01) and a decrease in JAK-2 and AKT activation. However, the intrinsic angiogenic function of BMDACs, including VEGF secretion and promotion of endothelial cell tubule formation, was preserved with aging. Furthermore, facilitated mobilization of old bone marrow-derived mononuclear cells to the ischemic hindlimb by intramuscular injection enhanced ischemia-induced neovascularization in old mice in vivo (p < 0.001). Conclusions: The age-related impairment in ischemia-induced neovascularization is largely attributable to a marked attenuation of BMDAC mobilization with a preservation of intrinsic angiogenic function with age.